Amino-functionalized CdSe/ZnS quantum dot-based lateral flow immunoassay for sensitive detection of aflatoxin B1. Issue 29 (10th July 2018) - Li, Jieying; Mao, Mao; Wu, Feng; Li, Qiang; Wei, Luyao; Ma, Lan
Abstract : In this study, highly fluorescent amino-functionalized CdSe/ZnS QDs coated with amphiphilic N -alkylated poly(ethyleneimine) have been synthesized and applied as fluorescent probes in LFIA strips for on-site determination of AFB1. Abstract : In this study, highly fluorescent amino-functionalized CdSe/ZnS core/shell quantum dots (CdSe/ZnS QDs) coated with amphiphilic N -alkylated poly(ethyleneimine) have been synthesized and applied as fluorescent probes in lateral flow immunoassay (LFIA) strips for on-site determination of aflatoxin B1 (AFB1). The amino-functionalized QDs were used to combine with anti-AFB1 via thiol-maleimide conjugation and they effectively enhanced the detection sensitivity. The test strip had high sensitivity for AFB1 from 0.001 ng mL −1 to 10 ng mL −1 with a low limit of detection (LOD) of 0.005 ng mL −1, which was much lower than the allowable concentration by the European Commission (EC) (2.0 μg kg −1 ) and FDA (20 μg kg −1 ). The IC50 value was calculated to be 0.025 ng mL −1 . The reproducibility and recovery tests showed that the quantitative results were accurate, and it could be used for rapid on-site detection of AFB1 in cereal products.